2011
DOI: 10.1111/j.1540-8175.2010.01256.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bisphosphonates on the Progression of Degenerative Aortic Stenosis

Abstract: Bisphosphonates appear to regulate mineralization in both bone and vasculature. Degenerative aortic stenosis (AS) is thought to be due to vascular calcification. We studied the effect of bisphosphonates on the progression of degenerative AS. A retrospective study was performed on patients >70 years, who had transthoracic echocardiograms (TTE) >1 year apart and an initial aortic valve area (AVA) of 0.6-2.0 cm². Patients were excluded if they had an ejection fraction <40%, other significant valvular or congenita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…The effect of osteoporosis therapy has been investigated because of an association between aortic valve calcification and low skeletal bone mineral density (Aksoy et al, 2005). Several small observational studies demonstrated a possible link between use of bisphosphonates and slowing of AVS progression (Skolnick et al, 2009;Sterbakova et al, 2010;Innasimuthu and Katz, 2011), although such beneficial effects may be not remarkable in older women (Aksoy et al, 2012). Taken together, prospective randomized clinical studies are certainly needed to evaluate the role of regulation of calcium and phosphate metabolism for preventing progression of CAVD especially at its early stage.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of osteoporosis therapy has been investigated because of an association between aortic valve calcification and low skeletal bone mineral density (Aksoy et al, 2005). Several small observational studies demonstrated a possible link between use of bisphosphonates and slowing of AVS progression (Skolnick et al, 2009;Sterbakova et al, 2010;Innasimuthu and Katz, 2011), although such beneficial effects may be not remarkable in older women (Aksoy et al, 2012). Taken together, prospective randomized clinical studies are certainly needed to evaluate the role of regulation of calcium and phosphate metabolism for preventing progression of CAVD especially at its early stage.…”
Section: Discussionmentioning
confidence: 99%
“…This theory is supported by small retrospective studies reporting delay in loss of valve area 18, 19 . However, in a large retrospective analysis of 801 females (mean age 76 years) with mild to moderate AS, bisphosphonates failed to impact AS progression after >5years 20 ; survival and AVR rate were unaffected over >3 years 20 .…”
Section: Bisphosphonatesmentioning
confidence: 79%
“…Optimal management strategies depend on AS stage, severity, and symptoms. Options for medical management are limited, as studies have failed to elucidate treatments that retard or reverse disease progression . Despite theoretical concerns with afterload‐reducing agents in patients with symptomatic severe AS, use of these agents has not been shown to compromise cardiac output.…”
Section: Aortic Stenosismentioning
confidence: 99%